2020
DOI: 10.1111/ajo.13217
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of surgical outcomes using Gyrus PKS™ vs LigaSure™ in total laparoscopic hysterectomy: A randomised controlled trial

Abstract: Background Advanced vessel sealing devices are widely used in laparoscopic surgery. However, there remains a lack of adequately powered trials comparing laparoscopic advanced vessel sealing devices in the clinical setting, especially in gynaecology. Aims This single‐blinded randomised controlled trial aims to compare the surgical outcomes of total laparoscopic hysterectomy (TLH) using either the Gyrus PKS™ LYONS dissecting forceps or the LigaSure™ Maryland jaw vessel sealer/divider. Materials and Methods Women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…One study [ 24 ] was excluded from 15 studies [ 5 , 6 , 24 36 ], because it did not report data on relevant outcomes. Seven studies did not compare ABVS devices with conventional bipolar systems [ 6 , 25 , 27 , 28 , 31 , 33 , 34 ], two studies included hysterectomies for malignant indication [ 35 , 36 ]. One study reported supracervical laparoscopic hysterectomies [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study [ 24 ] was excluded from 15 studies [ 5 , 6 , 24 36 ], because it did not report data on relevant outcomes. Seven studies did not compare ABVS devices with conventional bipolar systems [ 6 , 25 , 27 , 28 , 31 , 33 , 34 ], two studies included hysterectomies for malignant indication [ 35 , 36 ]. One study reported supracervical laparoscopic hysterectomies [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding total operative time, the observed reduction of 8 min did not allow us to suggest an economic advantage provided using ABVS devices in TLH. Considering the average cost of a standard operative room (5 Euro/minute) [ 5 , 34 ] and the higher cost of an ABVS device compared to conventional bipolar instruments, we could estimate the need for a 20–30 min reduction in total operative time to balance the increased expense [ 5 , 37 ]. One included study reported data stratified per learning curve [ 26 ].…”
Section: Discussionmentioning
confidence: 99%